Vertical Integration and Firm Productivity. Issue 2 (1st November 2016) - Li, Hongyi; Lu, Yi; Tao, Zhigang
Abstract : This paper uses three cross‐industry datasets from China and other developing countries to study the effect of vertical integration on firm productivity. Our findings suggest that vertical integration has a negative impact on productivity, in contrast to recent studies based on U.S. firms. We argue that in settings with poor corporate governance, vertical integration reduces firm productivity because it enables inefficient rent‐seeking by insiders.